Antitesticular activities of different solvent fractions from hydro-methanol (2:3) extract of Cuminum cyminum in albino rat: A Comparative analysis - Bhabani Prasad Pakhira; Abhinandan Ghosh; Adrija Tripathy; Debidas Ghosh (International Journal of Phytomedicine, 2017)
Currently available contraceptives are associated with adverse effects. So, search on safer agents in this purpose is one of the priority areas of WHO. Our previous study showed a significant antifertility effect of hydro-methanol extract of Cuminum cyminum Linn (Umbelliferae) in male albino rat. The main objective of this work isto search outthe potentfraction of hydro-methanol extract of seed of Cuminum cyminum in adult male albino rat for the development of herbal male contraceptive to reduce the bio-burden of phytomolecules. The n-hexane, chloroform, ethyl acetate, and n-butanol fractions of the hydro-methanol (2:3) extract of seed of Cuminum cyminum were administrated orally to male rat. Results showed the maximum antitesticular activity of chloroform fraction (CH-Fr) than other fractions included here. Treatment with CH-Fr fraction resulted a significant inhibition in spermiological parameters, activities of testicular androgenic key enzymes and antioxidative enzymes, levels of serum testosterone and seminal vesicular fructose, number of different generations of germ cells at stage VII of spermatogenic cell cycle and seminiferous tubular diameter (STD) along with significant increase in the level of testicular cholesterol in respect to the control. Significant upward and downward expression in Bax and Bcl-2 gene of male germ cells were indicated which focussed the sperm apoptotic enhancer activities of the fraction. The findings indicated that among the said four different fractions, the chloroform fraction of the hydro-methanol extract of the seed of Cuminum cyminum had most effective antitesticular activity.